TANGGUNG JAWAB BANK ATAS HASIL LELANG EKSEKUSI HAK TANGGUNGAN YANG DIBATALKAN PENGADILAN (Studi Putusan Nomor 24/Pdt.Bth/2017/PN Stb) - Subhan Amnan (Magister Hukum Universitas HKBP Nommensen, 2022)
The main activity of the Bank in general is to collect as much funds as possible from the public in the form of savings, and then manage these funds to be redistributed to the public in the form of loans or credits. In order to be able to carry out the granting of credit, there must be an agreement or credit agreement between the Bank as a creditor and the customer receiving credit as a debtor, using the terms and conditions mutually agreed upon by both parties in the credit agreement. The problems in this research are: how is the responsibility of the Bank for the auction of mortgage executions that have been canceled by the Court, how is the analysis of the judge's legal considerations in the decision Number 24/Pdt.Bth/2017/PN STP on the execution of mortgage auction objects that cannot be controlled by the winner auction, How is the legal protection for the winner of the mortgage auction for the execution of the auction object that cannot be controlled due to a court decision. This research is normative in nature, therefore research is needed which is a main plan in the development of science. This method is done by researching library materials or secondary data as the basic material for research The results show: there are two factors that influence the cancellation of mortgage auctions by the stabat district court, namely internal factors and external factors. Internal factors, such as: The parties who were not present during the trial which made the judge conclude that the parties did not have good faith in the trial so that the district court judge canceled the results of the mortgage auction. External factors, such as: where the bank auctions the mortgage object below the limit value of the object so that it does not match the value of the auction object so that the judge cancels the execution of the mortgage auction. The legal consequence of the cancellation of the mortgage auction is that the auction winner cannot control the object of the mortgage auction so that the auction winner gets a loss for the execution of the auction.